Earnings quality at initial public offerings in China - REN, Shaohong (2016)
This paper examines earnings management during IPO process in the Chinese context. Disagreeing with previous research, this study finds that IPO firms are not motivated to manage earnings upward before IPO. Managers are inclined to overstate the earnings of IPO year and these inflated earnings would be reversed after issuing. Those firms that conduct more aggressive earnings management at IPO year are more likely to experience post-issue accounting performance deterioration. Two of CSRC regulations are tested to investigate whether they could influence earnings management before IPO or not. The results indicate that the minimum net income requirement may no longer be a motivation of pre-IPO earnings management and the intangible assets proportion limitation could constrain earnings management through R&D to some extent.